Selection of microorganisms for ethanol production from cashew apple juice - Trakul Prommajak (2019)
© 2019, All Right reserved. Cashew apple is an agricultural waste generated by cashew nut industry at approximately 13 million tons per year worldwide. Toal sugars content of cashew apple juice was about 10% (w/v) which comprised 45.87 ± 0.94 g L-1 glucose and 45.22 ± 0.48 g L-1 fructose. These sugars could be used as substrates for ethanol fermentation. The presence of tannin in the juice limited the growth of some microorganisms. Thus, selection of suitable microbial strains which can produce ethanol in cashew apple juice medium is required. In this study, 50 microbial strains in the genera of Saccharomyces spp., Candida spp., Klebsiella spp., Zymomonas spp., Kluyveromyces spp. and Escherichia spp. were inoculated in cashew apple juice without tannin precipitation. The sample was taken out after fermentation for 24 and 48 h. Four microbial strains, including S. ellipsoideus TISTR 5194, S. ellipsoideus TISTR 5199, C. krusei TISTR 5624 and S. cerevisiae UNSW 706900, could produce ethanol at the level higher than 30 g L-1 after 48 h of fermentation period. Among these potential strains, C. krusei TISTR 5624 had the highest ethanol productivity (1.31±0.04 g L-1h-1) and ethanol yield of 35.14±0.1.21 g L-1 which were appropriate for ethanol production from cashew apple juice.